INVESTIGATING VARIOUS FACTORS TO INCREASE THE STRENGTH OF ALUMINA NANO-FIBERS USING SOL-GEL METHOD: Life Sciences-Bio Material - ALIREZA SAMADI TABRIZI (International Journal of Life Science and Pharma Research, 2022)
Aluminum fibers are important due to their high strength and resistance against metals and non- oxide materials slag, chemical stability up to 1000, low heat generation, and appropriate electrical cinsulation. The most important alumina fibers are used as metal or ceramic reinforcement and cause the improvement of physical and mechanical properties. Therefore, it is necessary to provide high strength fiber with appropriate shape. The purpose of the present study is to add these materials and reach the best fibers in terms of shape, strength and diameter through sol-gel method. Hence, we attempt to investigate various factors effect and obtain strong fibers using sol- gel method.